Increasing Patient Self-Enrollment in the National Amyotrophic Lateral Sclerosis Registry: Lessons Learned From a Direct to Provider Campaign. (February 2020) - Rechtman, Lindsay; Jordan, Heather; Kaye, Wendy; Ritsick, Maggie; Mehta, Paul
Objective: To conduct educational and promotional outreach activities to general neurologists and to increase self-enrollment of persons with amyotrophic lateral sclerosis (ALS) in the National ALS Registry (Registry). Methods: A multicomponent project to educate neurologists and increase Registry self-enrollment was delivered. Project components consisted of phone calls, mailings, train-the-trainer presentations, and key informant interviews. Project-specific metrics, continuing education enrollment, and Registry self-enrollment data were analyzed to measure project efficacy. Results: Mailings were sent to 1561 neurologists in 6 states during 2015 to 2016. Sixty-five percent of responding neurologists remembered the mailing 3 months after receipt. Of providers who saw patients with ALS in the 3-month period, 60% read the provider guide, 22% distributed a patient guide, and 15% advised a patient to self-enroll. No changes in self-enrollment rates were observed. Conclusion: Targeted mailings to providers can be used to educate them about the Registry; however, most providers did not distribute materials to patients with ALS. Increases in providers receiving Registry material did not lead to increases in patient self-enrollment. Practice Implications: General neurologists have competing priorities, and they see patients with ALS infrequently. Neurologists could be the appropriate channel to distribute Registry information to patients, but they are not the appropriate resource to assist patients with self-enrollment. Engaging the support staff of busy specialists can help increase research response rates and information distribution. The lessons learned from this project can be applied to other rare conditions and disease specialists.